2021
DOI: 10.1186/s12935-021-02215-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the prognostic value of a 2-gene signature of the WNT gene family in UCEC using bioinformatics and real-world data

Abstract: Background The WNT gene family plays an important role in the occurrence and development of malignant tumors, but its involvement has not been systematically analyzed in uterine corpus endometrial carcinoma (UCEC). This study aimed to evaluate the prognostic value of the WNT gene family in UCEC. Methods Pan-cancer transcriptome data of the UCSC Xena database and Genotype-Tissue Expression (GTEx) normal tissue data were downloaded to analyze the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…As far as we know, the TNM system was the most reliable predictive method for the prognosis of UCEC patients. Although some prognostic signatures had been identified for the prognosis of UCEC patients (Hu et al, 2021;Weijiao et al, 2021), these prognostic signatures had not been used for the prognosis of UCEC patients clinically. The current study identified the first cuproptosis-related prognostic signature for UCEC patients, which may be used for the prognosis prediction of UCEC patients clinically.…”
Section: Lncrna-mirna-mrna Cerna Network Analysismentioning
confidence: 99%
“…As far as we know, the TNM system was the most reliable predictive method for the prognosis of UCEC patients. Although some prognostic signatures had been identified for the prognosis of UCEC patients (Hu et al, 2021;Weijiao et al, 2021), these prognostic signatures had not been used for the prognosis of UCEC patients clinically. The current study identified the first cuproptosis-related prognostic signature for UCEC patients, which may be used for the prognosis prediction of UCEC patients clinically.…”
Section: Lncrna-mirna-mrna Cerna Network Analysismentioning
confidence: 99%
“…Furthermore, we validated the performance differences between our signature and other previously reported gene signatures in EC. The AUC of present protein signature for 1, 3 and 5 year OS prediction was higher in comparison with Hu's signature [ 23 ], Huang's signature [ 24 ], Liu's signature [ 25 ] and Qin's signature [ 26 ] (Fig. S 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…Despite these findings, some other studies have been conducted on UCEC thus far. Based on the WNT metabolic gene family, UCEC was classified into two subtypes using real-world data ( Hu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%